Loop Integrals in Three Outstanding Gauges: Feynman, Light-Cone, and Coulomb - Suzuki, Alfredo T. [UNESP]; Schmidt, Alexandre G. M. [UNESP] (Elsevier, 2001)
We apply the negative dimensional integration method (NDIM) to three outstanding gauges: Feynman, light-cone, and Coulomb gauges. Our aim is to show that NDIM is a very suitable technique to deal with loop integrals, regardless of which gauge choice that originated them. In the Feynman gauge we perform scalar two-loop four-point massless integrals; in the light-cone gauge we calculate scalar two-loop integrals contributing to two-point functions without any kind of prescriptions, since NDIM can abandon such devices - this calculation is the first test of our prescriptionless method beyond one-loop order; and finally, for the Coulomb gauge we consider a four-propagator massless loop integral, in the split-dimensional regularization context. © 2001 Academic Press.
Keywords: Dimensional regularization; Light-cone and Coulomb; Negative dimensional integration; Noncovariant gauges; Quantum field theory